Feeding Ecology of Pachypterus atherinoides (Actinopterygii; Siluriformes; Schilbeidae): A Small Freshwater Fish from Floodplain Wetlands of Northeast India - Gogoi Budhin; Das Debangshu Narayan; Saikia Surjya Kumar (Croatian Journal of Fisheries, 2020)
The feeding ecology of Pachypterus atherinoides was investigated for two consecutive years (2013-2015) from floodplain wetlands in the Subansiri river basin of Assam, North East India. The analysis of its gut content revealed the presence of 62 genera of planktonic life forms along with other animal matters. The organization of the alimentary tract and maximum Relative Mean Length of Gut (0.511±0.029 mm) indicated its carnivorous food habit. The peak gastro-somatic index (GSI) in winter-spring seasons and summer-rainy seasons indicated alteration of its feeding intensity. Furthermore, higher diet breadth on resource use (Levins’ and Hurlbert’s) with zooplankton compared to phytoplankton and total plankton confirmed its zooplanktivore habit. The feeding strategy plots also suggested greater preference to zooplankton compared to phytoplankton. The organization of its gill rakers specified a secondary modification of gut towards either carnivory or specialized zooplanktivory. So, the fish may be a carni-omnivore with preference to zooplankton.